2006
DOI: 10.15666/aeer/0402_055061
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of the Af Rcwheat2 Wheat Growth Simulation Model in Hungary

Abstract: Harnos: Applicability of the AFRCWHEAT2 wheat growth simulation model in Abstract. The aim of the present work was to determine the applicability of the AFRCWHEAT2 wheat growth model under Hungarian conditions. The Farquhar model, which, when properly calibrated, gives a satisfactory description of the net photosynthesis of Hungarian winter wheat varieties at various atmospheric CO 2 concentrations, temperatures and light conditions, was incorporated into the model. Both the original AFRCWHEAT2 model and the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Suitable predicting of Soybean biomass in different sowing date showed that this traits in this model could be predicted well dry matter production in basis of uptake of sun radiation by plants green cover, maximum and minimum temperature, in potential growth condition. According to Harnos (2006), CROPGRO-Soybean model could be predicted well biomass in 9 different zones, variation dimension of R 2 obtained to 0.98-0.95.…”
Section: Discussionmentioning
confidence: 90%
“…Suitable predicting of Soybean biomass in different sowing date showed that this traits in this model could be predicted well dry matter production in basis of uptake of sun radiation by plants green cover, maximum and minimum temperature, in potential growth condition. According to Harnos (2006), CROPGRO-Soybean model could be predicted well biomass in 9 different zones, variation dimension of R 2 obtained to 0.98-0.95.…”
Section: Discussionmentioning
confidence: 90%
“…Plant growth models with various degrees of complexity have been elaborated for the use of plant growers and breeders, ranging from simple statistical regression models to models with a complicated mechanism, capable of simulating anything from a simple process to the behavior of the whole plant (Harnos, 2006). In addition to experimental research, many scientists also use simulation models to gain a better understanding and description of environmental stress effects, such as high temperature, drought stress, and their effects on the development and yield of plants grown at elevated atmospheric CO 2 concentration.…”
Section: Wheat Growth Model Simulationmentioning
confidence: 99%